Sistem Informasi Laporan Keuangan Persediaan Barang Menggunakan Metode FIFO Berbasis Web Pada PT. Usaha Maju - Hesti Ayu Pangastutik; Ahmad Ashifuddin Aqham; Haris Ihsanil Huda (Jurnal Mahasiswa Kreatif, 2023)
Usaha Maju is a private company engaged in trading. This company has been around for a long time in Gempolsewu Dk Tegal Kapang District, Rowosari District, Kendal Regency, which is adjacent to TPI Tawang. Usaha Maju does not yet have an information system to assist companies in recording financial statements and merchandise inventory. In managing the old report data, it is still done manually, namely using a notebook in recording the data. data processing is carried out twice, namely when purchasing goods and at the time of sale, resulting in less effectiveness in bookkeeping and financial reporting in the company. Recording of inventory financial reports is still often the difference between the financial statements of purchases and sales. With the problems and background above, the authors finish by implementing the "Inventory Information System Using the Web-Based Fifo Method at PT. Forward Enterprises” in order to facilitate the company in recording the Financial Statements of inventory and also improve companies in the field of Technology. This application uses sublime text 3 software as a text editor and MySQL database.